Study of a 1 eV GaNAsSb photovoltaic cell grown on a silicon substrate - Tan, K. H. (2014)
We report the performance of a 1 eV GaNAsSb photovoltaic cell grown on a Si substrate with a SiGe graded buffer grown using molecular beam epitaxy. For comparison, the performance of a similar 1 eV GaN0.018As0.897 Sb 0.085 photovoltaic cell grown on a GaAs substrate was also reported. Both devices were in situ annealed at 700 °C for 5 min, and a significant performance improvement over our previous result was observed. The device on the GaAs substrate showed a low open circuit voltage (VOC) of 0.42 V and a short circuit current density (JSC) of 23.4 mA/cm2 while the device on the Si substrate showed a VOC of 0.39 V and a JSC of 21.3 mA/cm2. Both devices delivered a quantum efficiency of 50%–55% without any anti-reflection coating.